2016
DOI: 10.17475/kujff.03251
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone (PCL) based polymer composites filled wheat straw flour

Abstract: In this study, polycaprolactone (PCL) based polymer composites were manufactured through injection moulding machine. Polycaprolactone (PCL) and wheat straw flour was used as polymer matrix and organic filler respectively. The effects of wheat straw flour loading on the mechanical properties of the manufactured composites were investigated. The thermal behaviors (TGA and DSC), mechanical properties (tensile, flexural and impact strength), of manufactured composites were determined. According to test results, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Composite densities were increased with the addition of lignocellulosic materials due to their higher cell wall densities. Similar results were also reported by others (Stokke et al 2014;Karakuş and Mengeloğlu 2016;Çavuş and Mengeloğlu 2016;Mengeloğlu and Çavuş 2019). In the case of filler type, both MIP and WF as fillers increased the density of the composites, but at high filler levels, this increase was more pronounced for MIP filled ones (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Composite densities were increased with the addition of lignocellulosic materials due to their higher cell wall densities. Similar results were also reported by others (Stokke et al 2014;Karakuş and Mengeloğlu 2016;Çavuş and Mengeloğlu 2016;Mengeloğlu and Çavuş 2019). In the case of filler type, both MIP and WF as fillers increased the density of the composites, but at high filler levels, this increase was more pronounced for MIP filled ones (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Statistical analysis showed that WF rates had significant effect on density (P < 0.0001). This increase was believed to be due to the higher cell wall density of lignocellulosic materials (Mengeloğlu and Karakuş 2012;Karakuş and Mengeloğlu 2016). This was because the density of the wood substance in the cell wall is about 1.5 g/cm 3 (Mäkinen et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Both filler increased density. This increase was due to the higher cell wall density of lignocellulosic Materials [13], [14]. Between RPF and OP fillers, RPF provided higher density values than OP filler.…”
Section: Resultsmentioning
confidence: 99%